Emergency contraception: awareness, use and choices amongst antenatal women in a South West Nigeria teaching hospital - Omotayo, Ramon S.; Akadiri, Olumide; Akintan, Adesina L.; Okunnuga, Ndidi A.; Gbala, Michael O.; Omotayo, Sade E.; Owa, Olorunfemi O. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Emergency contraception is a worthwhile innovation by all considerations in that it affords women of the opportunity to avert being pregnant even after sexual intercourse had occurred and they do not desire pregnancy or when an on-going contraceptive method is suspected to have failed. The study assessed the level of awareness, level of usage and the choices of emergency contraception among antenatal women. Method: Women that met the inclusion criteria were serially recruited as they came by convenient sampling method until the required number of 300 which included the allowance for attrition was completed. The questionnaire was administered to the consented patients by antenatal clinic nurses and intern doctors under the supervision of the researchers. Results: The mean age of the respondents was 34.5±3.2 years. More than half (52.7%) have never used contraceptives before. Almost half of the respondents 51.3% have not had any information about emergency contraceptives The major source of information about emergency contraception for the majority (42.7%) of the respondents was through their friends. Only 18.7% of the respondents have ever used emergency contraceptives before with postinor being the commonest used by 78.6% of them. Conclusions: It is part of the rights of women to control the number of children they desire and time they desire to give birth to them. There is need to improve on the awareness of emergency contraceptives among the study population in order to prevent morbidity and mortality related to unwanted pregnancy.